Early Brain Injury or Cerebral Vasospasm 2011
DOI: 10.1007/978-3-7091-0353-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Early Brain Injury After Subarachnoid Hemorrhage

Abstract: Nitric Oxide (NO) is the major regulator of cerebral blood flow. In addition, it inhibits platelet adherence and aggregation, reduces adherence of leukocytes to the endothelium, and suppresses vessel injury. NO is produced on demand by nitric oxide synthase and has a very short half life. Hence maintenance of its cerebral level is crucial for normal vascular physiology. Time dependent alterations in cerebral NO level and the enzymes responsible for its synthesis are found after subarachnoid hemorrhage (SAH). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 73 publications
(102 reference statements)
0
33
0
2
Order By: Relevance
“…EPOR, a member of the cytokinereceptor type I superfamily and is com-and ischemic neuronal damage (52). The main responsible agent in causing endothelial impairment appears to be either oxyhemoglobin or bilirubin (49), with oxyhemoglobin proposed as able to scavenge NO, inactivate guanylate cyclase (GC) or increase production of oxygen radicals.…”
Section: Erythropoietinmentioning
confidence: 99%
See 1 more Smart Citation
“…EPOR, a member of the cytokinereceptor type I superfamily and is com-and ischemic neuronal damage (52). The main responsible agent in causing endothelial impairment appears to be either oxyhemoglobin or bilirubin (49), with oxyhemoglobin proposed as able to scavenge NO, inactivate guanylate cyclase (GC) or increase production of oxygen radicals.…”
Section: Erythropoietinmentioning
confidence: 99%
“…Furthermore, after SAH, increased oxidative stress can uncouple eNOS via Zn 2+ thiolate oxidation, or, theoretically, by tetrahydrobiopterin depletion or oxidation, resulting in a paradoxical release of superoxide anion radical, further exacerbating oxidative stress and microvascular damage (51, Figure 2). To date, endothelial mechanisms are considered to be the main contributors to induced vasospasm (52). It has been reported that NO level decreases acutely within 10 min after SAH both in experimental models and in humans, leading cerebrovascular relaxation impairment…”
Section: Erythropoietinmentioning
confidence: 99%
“…Le NO joue un rôle important pharmacologique, immunologique, toxicologique et neurobiologique [38,39]. Le NO est produit à partir de la L-arginine par la NO synthase (NOS) endothéliale (eNOS), par la NOS neuronale (nNOS), respectivement dans l'intima et l'adventice des vaisseaux cérébraux, ainsi que par la NO synthase inductible (iNOS).…”
Section: Nounclassified
“…De façon schématique, il est possible de considérer une alté-ration triphasique des concentrations cérébrales de NO après une HSA : une première phase de 0 à 60 minutes après l'HSA, une deuxième phase d'une à six heures, et une troisième phase de 6 à 72 heures [38]. Les deux premières phases ont été étudiées dans les modèles expérimentaux animaux, alors que la troisième phase est documentée également chez l'homme.…”
Section: Nounclassified
“…40 Cerebral NO levels decrease in the first hours following subarachnoid hemorrhage and recover at 24 hours. 41 In the present study, we delivered NO at 30 minutes after subarachnoid hemorrhage. It is clear that NO-ELIP improved neurologic function after subarachnoid hemorrhage.…”
mentioning
confidence: 96%